Tne influence of the classic traditions to vagif’s poetry (Eurasian Journal of Philology Science and Education, 2018)
Just in this article it is said about the influence of classical traditions to Molla Panah Vagif’s activitywho was the famous master of the 18th century Azerbaijan poetry, he enriched our literature with the newand real poems. Let’s look through the literary scenery of the 18th century – the master’s living period inshort. In the 18th century the artistic, philosophical, scientific, ethic, aesthetic, social-political opinions,all activity potential of Azerbaijan nation were realized in the literature. During that time the leadingrole and position in Azerbaijan cultural life belonged to the literature. The unceasing social-political,economical crisis, the military contentions strengthened the concrete critical inclinations in the literature.The literary men paid attention to the negativities of the reality a lot and tried to criticize the sinners.Azerbaijan literary men acted as a historian, philosopher and publicist willingly or unwillingly.